ANALYSIS OF BPK LEGAL BASIS FOR FORESIGHT AUDITORS FOR THE ACCELERATED ACHIEVEMENT OF THE SUSTAINABLE DEVELOPMENT GOALS - Putra, Angga Kiryaditama (Badan Pemeriksa Keuangan Republik Indonesia, 2020)
Law Number 15 of 2004 and Law Number 15 of 2006 only lay down the authority of the BPK in conducting audits in general and the types of audits that can be conducted by BPK. These regulations, however, do not specifically and explicitly provide the authority to the conduct of a foresight audit. Foresight audit launched by BPK in the 2016-2020 BPK Strategic Plan will be very important in the achievement of sustainable development goals (SDGs) by 2030, given that the BPK will provide feedback and suggestions on important future policies to accelerate the achievement of SDGs. Legal instruments have an important role for BPK as the legal basis for the institution in achieving the Highest Maturity Model of the Accountability Organization in conducting a foresight audit. This study employs a normative legal research method that aims to explore and study regulations that support BPK as a foresight auditor in the future. The results illustrate that the legal basis or legal instruments for the exercise of BPK’s foresight audit authority is sufficient but still needs to be improved. The addition of legal instruments and authorities can be a solution to ensure that any foresight audit performed in the future can run optimally and accelerate the achievement of the SDGs.